2009
DOI: 10.1080/17405620802102947
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers begin to differentiate the times of events from throughout the lifespan

Abstract: Three-, 4-and 5-year-old children were presented with simple timelines of past and future and asked to place pictures representing different events at appropriate places. Events came from three rough temporal groupings for both past and future (24 hours, 12 months and several years). Placement of items in the categories improved with age. Three-year-olds placed events that occurred years ago further away on the past timeline than events that had occurred more recently, but they failed to discriminate between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 60 publications
0
40
1
Order By: Relevance
“…Developmental milestones appear to be achieved over the preschool years (Suddendorf and Moore, 2011; Suddendorf and Redshaw, in press). During this period, children begin to show competence on tasks requiring them to delay gratification for the future (Mischel et al, 1989; Moore et al, 1998; Garon et al, 2012), save resources for the future (Atance and Meltzoff, 2005; Metcalf and Atance, 2011), place multiple future episodes in time relative to each other (Friedman, 2000; Busby Grant and Suddendorf, 2009; Hayne et al, 2011; Hudson and Mayhew, 2011), learn a rule to be applied in the future (Kliegel and Jäger, 2007), plan an intervention that will help a character in the future (McColgan and Mccormack, 2008; McCormack and Hanley, 2011), and evaluate the likelihood of future events (Lagattuta and Sayfan, 2011). The current study documents the development of another key future-oriented capacity: adaptively linking past and deferred future episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental milestones appear to be achieved over the preschool years (Suddendorf and Moore, 2011; Suddendorf and Redshaw, in press). During this period, children begin to show competence on tasks requiring them to delay gratification for the future (Mischel et al, 1989; Moore et al, 1998; Garon et al, 2012), save resources for the future (Atance and Meltzoff, 2005; Metcalf and Atance, 2011), place multiple future episodes in time relative to each other (Friedman, 2000; Busby Grant and Suddendorf, 2009; Hayne et al, 2011; Hudson and Mayhew, 2011), learn a rule to be applied in the future (Kliegel and Jäger, 2007), plan an intervention that will help a character in the future (McColgan and Mccormack, 2008; McCormack and Hanley, 2011), and evaluate the likelihood of future events (Lagattuta and Sayfan, 2011). The current study documents the development of another key future-oriented capacity: adaptively linking past and deferred future episodes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Friedman (1991) showed that four-year-olds can judge the relative order of two unrelated events that occurred in their schools six weeks apart (a lesson on tooth brushing and a demo of how video cameras work). A number of other studies have also shown that fourand five-year-olds make some judgments about the order of unrelated events over extended time periods (Friedman, 2000;Friedman & Kemp, 1998;Friedman et al, 1995;Hudson & Mayhew, 2011;McCormack & Hanley, 2011), although children find it easier to order past than future events (Busby-Grant & Suddendorf, 2009;McCormack & Hanley, 2011). Some of these studies used a time line procedure whereby children had to place events at locations on a line stretching back into the past or forward into the future, and although children of this age are not perfect at this task, their above-chance performance suggests that they understood this format (Friedman & Kemp, 1998;Hudson & Mayhew, 2011;though see DroitVolet & Coull, 2015).…”
Section: Stage (C): Linear Event-independent Time (4-5 Years)mentioning
confidence: 98%
“…To our knowledge, although several studies have asked how children map time onto external spatial artifacts (e.g., Berteletti, Lucangeli, & Zorzi, 2012;Busby Grant & Suddendorf, 2009;Friedman, 2000Friedman, , 2002Friedman & Kemp, 1998;Hudson & Mayhew, 2011;Tillman, Marghetis, Barner, & Srinivasan, 2017), and others have examined the direction of children's counting (e.g., Göbel, McCrink, Fischer, & Shaki, 2018;Shaki, Fischer, & Göbel, 2012), only two previous studies have tested whether children produce LR representations of time in the absence of training or experimentally imposed artifacts that force the use of a line. One study (Dobel, Diesendruck, & Bölte, 2007) showed that while adults and literate children tended to represent the agent, object, and recipient in a verbally described event congruently with their reading/ writing direction, preschoolers did not show this bias.…”
Section: Research Highlightsmentioning
confidence: 99%